"A Shameless Ideology of Shameless Women": Positioning the Other in Social Media Discourse Surrounding a Women's Rights Movement in Pakistan. (March 2022) - Sadaf, Shomaila; Siitonen, Marko
This study analyzes social media (YouTube) discourse related to Aurat March 2019, a women's rights movement in Pakistan. Using a discourse analytical approach that draws on the premises of Positioning theory, the analysis reveals the following two major storylines from the data: "The women who stray from the path, and the men who will return them to it, " and "Islam under threat from the outside." Social media platforms allow their users to express opinions in online spaces, often resulting in polarization and clustering of like-minded people in so-called echo-chambers. This study demonstrates how social media users actively participate in the discursive construction of the "other, " and how the women's rights movement in Pakistan continues to struggle against hegemonic scripts of gender and sexuality.